2002
DOI: 10.2169/internalmedicine.41.408
|View full text |Cite
|
Sign up to set email alerts
|

Successful Diagnosis Using Scab for PCR Specimen in Tsutsugamushi Disease.

Abstract: Wetreated a case of Tsutsugamushi disease diagnosed by polymerase chain reaction (PCR) using a scab specimen at the bite site of trombiculid mites. Otherwise the diagnosis could not be confirmed by serum antibody test nor the PCRtest of blood. The genome of Rickettsia tsutsugamushi was detected and identified as the Kawasaki serotype strain. Anattempt to extract the genomefrom the scab has not been reported, thus our data suggest that the scab is a useful specimen to confirm the diagnosis of Tsutsugamushi dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, PCR amplification of O. tsutsugamushi DNA from blood often lacks sensitivity because some hemoglobin, iron porphyrin, and other factors may inhibit the PCR, although obtaining and processing the blood that avoids the inhibitors is possible ( 3 , 4 , 9 ). Ono et al previously found O. tsutsugamushi DNA (identified as Kawasaki type) in only 1 patient's eschar before antimicrobial drug treatment but not in the acute-phase blood sample ( 9 ). In the present study, 7 scrub typhus patients were examined, and O. tsutsugamushi DNA was successfully detected in their spontaneously desquamated eschars and acute-phase blood samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PCR amplification of O. tsutsugamushi DNA from blood often lacks sensitivity because some hemoglobin, iron porphyrin, and other factors may inhibit the PCR, although obtaining and processing the blood that avoids the inhibitors is possible ( 3 , 4 , 9 ). Ono et al previously found O. tsutsugamushi DNA (identified as Kawasaki type) in only 1 patient's eschar before antimicrobial drug treatment but not in the acute-phase blood sample ( 9 ). In the present study, 7 scrub typhus patients were examined, and O. tsutsugamushi DNA was successfully detected in their spontaneously desquamated eschars and acute-phase blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…tsutsugamushi Sta56 gene in blood samples or isolates from patients ( 3 – 8 ). However, the test often gave a false-negative result because hemoglobin and other components in blood may inhibit PCR amplification ( 3 , 4 , 9 ). The commonly seen eschars in scrub typhus patients were suggested as alternative specimens for diagnosis ( 9 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This result may involve a nonspecific reaction. Several reports have shown that eschar from a scrub typhus patient can be used as a diagnostic specimen for detecting O. tsutsugamushi DNA (6–8). In this study, we demonstrated the usefulness of pUC‐iTSG56 and pUC19‐Posi as positive controls in PCR for detecting O. tsutsugamushi DNA in an eschar specimen (Fig.…”
Section: Oligonucleotides Used In This Studymentioning
confidence: 99%
“…Sporadic case reports and anecdotal evidence have demonstrated the clinical course of patients with this disease (1,11,15), and have described a delay in the diagnosis leading to severe complications in some cases (1). However, data on the actual incidence of various complications or mortality associated with Tsutsugamushi disease are scarce (2).…”
Section: Introductionmentioning
confidence: 99%